1999
DOI: 10.1007/s007020050230
|View full text |Cite
|
Sign up to set email alerts
|

GABA transporters (GAT-1) in Alzheimer's disease

Abstract: The presynaptically located gamma-aminobutyric acid (GABA) transporter (GAT-1) was studied in a group of patients with Alzheimer's disease (AD) and in a control group using the GAT-1 selective radioligand [3H]tiagabine. Post mortem brain tissue from frontal cortex, temporal cortex, and caudate nucleus from 18 AD patients and 23 age-matched controls were studied. The binding was saturable (Kd 26 nM) and region specific. There were no significant differences between the groups with respect to the binding capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…16 In contrast, biochemical investigations of biopsy brain tissue from patients in the early phases of AD have not shown significant alterations in the concentration of GABA 44,46 and no disturbance of GABA transporters. 47,48 It is possible, therefore, to conclude that the motor cortex hyperexcitability of AD is not caused by the dysfunction of GABAergic intracortical inhibitory circuits. 16,17 Motor programming and execution is based on a distributed network with replicated topographic organization of the same body district (particularly for hand and finger control) which has been considered of importance in motor learning and in functional recovery after partial lesions of the motor brain centers.…”
Section: Discussionmentioning
confidence: 97%
“…16 In contrast, biochemical investigations of biopsy brain tissue from patients in the early phases of AD have not shown significant alterations in the concentration of GABA 44,46 and no disturbance of GABA transporters. 47,48 It is possible, therefore, to conclude that the motor cortex hyperexcitability of AD is not caused by the dysfunction of GABAergic intracortical inhibitory circuits. 16,17 Motor programming and execution is based on a distributed network with replicated topographic organization of the same body district (particularly for hand and finger control) which has been considered of importance in motor learning and in functional recovery after partial lesions of the motor brain centers.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it has been suggested that GABAergic circuits in the cerebral cortex of AD are relatively well preserved when compared with circuits that use other neurotransmitters systems (Young, 1987; Lowe et al, 1988; Reinikainen et al, 1988; Ferrer et al, 1991; Hof et al, 1991; Nägga et al, 1999; Rissman et al, 2007). However, alterations of neurons labeled for parvalbumin were identified in the cerebral cortex of AD patients in several studies (Fonseca et al, 1993; Solodkin et al, 1996; Brady and Mufson, 1997; Mikkonen et al, 1999), which are responsible for most of the GABAergic pericellular innervation of pyramidal cells (basket and chandeliers cells).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study in which human APP was expressed in rat hippocampal neurons using a viral expression system, no change in GABAergic transmission was observed, while both AMPA and NMDA receptor-mediated transmission was impaired (Kamenetz et al, 2003). In addition, postmortem studies using AD brain tissue, indicate that GABAergic interneurons are relatively spared (Nagga et al, 1999). Taken together, these studies suggest the overexpression of A␤ has a limited effect of GABAergic interneurons, and this is supported by the findings reported here.…”
mentioning
confidence: 84%